Loss analysis of quasi Z‐source inverter with Superjunction‐MOSFET. Issue 2 (23rd July 2018) - Kamoshida, Naoki; Iijima, Ryuji; Isobe, Takanori; Tadano, Hiroshi
Abstract: A Z‐source inverter (ZSI) can work as an inverter with boost capability in one stage by using its impedance source and the short‐through mode as the switching mode. This paper discusses the circuit losses that depend on the boost ratio between the quasi ZSI, which is one of the ZSI topologies, using Superjunction‐MOSFETs and the conventional inverter with a boost chopper using IGBTs. Two‐kilowatt class three‐phase inverter systems for an AC output of 200 V were fabricated using the proposed method and the conventional method, and the losses for each component were analyzed experimentally. Experimental results confirmed that the proposed method can reduce the total loss in low boost ratio operations, in comparison with the conventional method, due to its reduced inverter conduction loss.